How Healthy Is State Mental Health System in Madhya Pradesh, India? An Assessment of Today to Plan for a Better Tomorrow. (11th March 2021) - Kokane, Arun M.; Pakhare, Abhijit P.; Gururaj, Gopalkrishna; Varghese, Mathew; Benegal, Vivek; Rao, Girish N.; Anniappan Arvind, Banavaram; Prasad M, Krishna; Mitra, Arun; Shukla, Mukesh; Yadav, Kriti; Ray, Sukanya; et al.
Abstract : Background . Mental illness affects over one-third of the Indian population, and only a little is known about the exact situation of health systems in Madhya Pradesh, India. Therefore, the present research work provides an assessment of state mental health systems in Madhya Pradesh. Methods . The present cross-sectional study was conducted as a part of National Mental Health Survey 2015-16 in 48 districts of Madhya Pradesh, to provide an overview of the status of mental health systems. Secondary data was also retrieved from the state office so as to present the situational analysis in a more comprehensive and inferential way. The proforma for the study was developed based on the experience gained from studies conducted earlier with World Health Organization's Assessment Instrument for Mental Health Systems (WHO-AIMS) and with WHO's Mental Health Atlas as the base for thematic analysis. Results . Out of 51 districts, 13.7% of the districts of the state have been covered under District Mental Health Program (DMHP) in 2015-16. Around 11.8% of district/general hospitals were involved in providing mental health services. The availability of psychiatrist was 0.05 per Lakh population. Around 0.2% of the total health budget was allocated by the state for the last financial year for mental health. The overall average score of Madhya Pradesh in the assessment of qualitative indicators was 31 out of 100 in the year 2015-16. Conclusion . There is huge scope and an urgent need to increase mental healthcare facilities (with upgradation of existing one) along the availability of mental healthcare staff.